The secret lives of booksellers and librarians [large type] : true stories of the magic of reading - Patterson, James, 1947-; Eversmann, Matt (Little Brown and Company, 2024)
"Booksellers and librarians are superheroes, saving lives every single day. Here are their amazing, inspiring true stories as told to the greatest storyteller of our time, James Patterson. To be a bookseller or librarian... You have to play detective. Be a treasure hunter. A matchmaker. An advocate. A visionary. A person who creates 'book joy' by pulling a book from a shelf, handing it to someone and saying, 'You've got to read this. You're going to love it.' Step inside The Secret Lives of Booksellers and Librarians and enter a world where you can feed your curiosities, discover new voices, find whatever you want or require. This place has the magic of rainbows and unicorns, but it's also a business. The book business. Meet the smart and talented people who live between the pages--and who can't wait to help you find your next favorite book"--